Effect of site occupancy on the reduction of Eu3+ and tunable luminescence of CaLa4Si3O13:Eu phosphor. Issue 19 (1st October 2022) - Chen, Wanping
Abstract: A series of europium-ion doped CaLa4 Si3 O13 phosphors were synthesized by using a conventional high-temperature solid-state method. X-ray powder diffraction patterns and photoluminescence spectra were utilized to characterize the as-prepared phosphors. The phosphors show tunable luminescence owing to the existence of Eu 2+ and Eu 3+ emission. A typical emission maximum of Eu 2+ is about 460 nm, and Eu 3+ shows a predominant 5 D0 - 7 F2 transition emission. The emission of Eu 2+ shifts toward the long wavelength side with increasing doping concentration. The site occupancy of Eu 2+ and Eu 3+ is analyzed according to their luminescence behaviors. The Eu 3+ ion at the Ca 2+ site can be partially reduced to Eu 2+, but at the La 3+ site cannot be reduced. The controllable reducing of Eu 3+ is explained according to the crystal structure of the host. Utilizing site selection to control the reducing of Eu 3+ is considered as an alternative strategy to design novel Eu 3+ and Eu 2+ codoped inorganic phosphor.